440. Assessing Motivators and Barriers in Anal Cancer Screening for People with HIV. (15th December 2022) - Geba, Maria C; Kalluri, Divya; Cardenas, Benjamin; Mitchell, Emma; Flickinger, Tabor; Dillingham, Rebecca; Thomas, Tania A
Abstract: Background: There is a rising prevalence of anal cancer in people with HIV (PWH) with recent evidence showing efficacy of screening procedures in preventing progression to anal cancer. A recent retrospective cohort study in our Ryan White HIV/AIDS Program (RWHAP) clinic evaluating engagement and retention in anal cancer screening services identified a significant gap in engagement in care among those eligible. This highlighted a need to identify and address barriers to engagement in screening services. Methods: Semi-structured qualitative interviews were performed on people eligible for anal cancer screening in the RWHAP clinic at the University of Virginia. Participants were at least 35 years old and receiving HIV care in the clinic. Recruitment was carried out by convenience sampling via internal clinic advertising and a tailored mobile app. Interviews were constructed using the health belief model and themes explored included perceived risks, benefits, and barriers to screening, as well as self-efficacy and cues to action. Results: Prominent barriers to engaging in anal cancer screening services included lack of awareness about screening procedures and stigma associated with sexual practices and sexual orientation. Notable motivators to engaging in screening services were education and familiarity with cancer prevention as well as trust in RWHAP clinic providers and staff. Conclusion: Our findings highlight the importance of eliciting patient perspectives as a critical and powerful tool when evaluating and improving on a screening program's performance. There is a resounding need to promote awareness of anal cancer screening among PWH in order to empower those at risk to seek effective preventative services. Raising awareness will involve careful and thoughtful messaging to de-stigmatize and normalize anal cancer screening in PWH. Disclosures: Rebecca Dillingham, MD, MPH, WHT, INC: Advisor/Consultant.